Ploughing New Ground: Exploring the Critical Traits of Leaders of Farmer Producer Organizations - Patil, Sharvari; Mehta, Mita (Indian Journal of Extension Education, 2024)
Farmer Producer Organisations (FPOs) are a vital component of the agriculture sector, numerous many studies have been done on them. Earlier studies have mentioned that leadership is a significant concern in FPOs and emphasized the importance and necessity of strong leadership in FPOs. However, rare research has been done explicitly on FPO leadership. Hence, this study identifies critical traits of actively operating FPO leaders. The study was carried out from 2023-2024 and data used in this research were collected from April 01 to July 15, 2023. Snowball sampling was used to select the participants. The study used a qualitative approach. Twenty in-depth semi-structured interviews with FPO leaders were conducted in Maharashtra. Each interview was transcribed, and content analysis was done by ATLAS.ti 7.5.16 software to examine the data. Findings from the identified codes reveal that FPO leaders possess a few unique traits as it a new form of organization having a blend of corporate and cooperative organizations. These unique traits are convincing power, establishing personal relations with members, gaining farmers trust etc. The study’s findings will aid stakeholders in creating policies for selecting influential FPO leaders or training current leaders to enhance FPO outcomes.
Keywords: Agriculture; Collectives; FPO; Leadership; Qualitative analysis